When Good Governance Matters: Digital Auditing and Public Sector Audit Quality - Edy Supriyono; Yussri Sawani; Enny Susilowati Mardjono; Simon Nisja Putra Zai; Vicky Pratama Mahardika (JASF: Journal of Accounting and Strategic Finance, 2026)
Purpose: This study aims to examine the effects of Computer-Assisted Audit Techniques (CAATs), remote auditing, and professional scepticism on the quality of public sector audits, and to analyse the role of good governance moderation in these relationships. This study is important because digital-based public sector audits require governance support to enable technology and auditor judgment to improve public accountability. Method: This study uses a quantitative approach with auditors of the Supreme Audit Agency (BPK) in Central Java as respondents. The Sample used was 134 respondents. Data were obtained by distributing questionnaires. Data were collected through surveys and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4.0. Findings: The results indicate that remote auditing has a positive effect on the quality of public sector audits. In contrast, CAATs and professional scepticism had no direct effect. However, good governance has been shown to moderate the influence of CAATs, remote auditing, and professional scepticism on audit Quality. These findings suggest that audit technology and auditors' critical attitude do not work automatically but require strong governance support. Implications: The results of this study affirm the importance of strengthening digital audit governance, data Quality, Information System Integration, digital Evidence security, auditor independence, and follow-up of audit results. BPK needs to build a digital audit ecosystem that is not only focused on technology adoption but also on strengthening accountability and internal controls. Novelty/Value: This study demonstrates that good governance is a key condition for the effectiveness of audit technology and for professional scepticism in improving the quality of public sector audits.